Online Business Site Quality Assessment - Chaitanya Krishna, B; Sai Mounish, P; Vinay Kumar, U; Divya Mallika, A (International Journal of Engineering and Technology, 2018)
Online business is seen as a splendid alternative for associations to accomplish new customers. Now and again, various web-based business destinations will be small life time. The achievement of the small stores will be having some minor issues majorly on the quality metrices of the product, as it will a flighty game plan. Our paper portrays the pertinent game plan of online business site quality metrics in view of writing. Research was endeavored to affirm and set up the appropriate essential of those qualities. The results are gained from an item quality assessment demonstrateÂ Â